New airfoil families for horizontal-axis wind turbines - Abdelrahman, Mohammad; Hassanein, Atef (2011)
It is found that the usage of conventional aircraft airfoil sections is not the proper choice for wind applications due to the difference in design objectives and the environment of application. Adopted aircraft airfoils for horizontal-axis wind turbines including NACA 44XX and NACA 230XX have experienced problems related to the high sensitivity to roughness effects which leads to decrease in maximum lift coefficient and increase in profile drag and hence large deviations in power curves and high losses in the annual energy production. The new trend towards overcoming these problems is to develop special-purpose airfoil families that could meet the requirements of wind energy. Two airfoil families have been developed to meet the design requirements. The first is a thin family named AERO 90XX, suitable for medium blades. The second family is a thick one named AERO 80XX, suitable for large blades. Finally, the superiority of the two families has been verified by applying them on real rotors and the performance calculation has shown a promising increase in the total annual energy production.